Republic of Belarus : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2005)
This Report on the Observance of Standards and Codes (ROSC) data module provides an assessment of the Republic of Belarus's macroeconomic statistics against the recommendations of the Special Data Dissemination Standard (SDDS) complemented by an assessment of data quality based on the IMF's Data Quality Assessment Framework. The assessment reveals that the quality of the Belarus macroeconomic statistics has improved significantly in many areas in the last few years. The authorities have also established a relatively good track record of implementing recommendations of past technical assistance in statistics.